A highly efficient solution of off-sunshine solar air heating using two packed beds of latent storage energy. (October 2017) - Arfaoui, Nessim; Bouadila, Salwa; Guizani, Amenallah
Highlights: A new solar air heater collector using a phase change material. Experimental study of the new solar air heater collector with latent storage. Energy analysis of the solar heater with latent storage collector. Nocturnal use of solar air heater collector. Abstract: In order to increase the efficiency of the solar air collector and to improve their thermal efficiency in terms of operating time, hot outlet air temperature and starting operation time, the performance of a compact phase change material solar air heater collector based on latent heat storage energy was investigated. In this solar collector, the two-packed bed absorber unit performs two functions: absorbing the solar energy and storing the thermal heat onto PCM. The solar energy was stored as sensible heat and latent heat in the encapsulated PCM as spherical capsules forms. The experimental apparatus designed and realized in the Research and Technology Center of Energy (CRTEn) in Tunisia. Moreover, the solar air heater with PCM is used only at night on natural convection mode. To assess the performances of the collector, outdoor experiments was carried out to validate the availability of using this solar collector for air heating application. During the experimental test, the inlet and outlet air temperature, the relative humidity, external wind speed, the global solar radiation and the PCM temperature distribution in different bed of the solar collector were recorded. The experimentally obtained measurements are used to analyze the performance of the PCM system, the thermal instantaneous stored, absorbed and useful energy during the charging and discharge process was calculated. The experimental results showed that in the charging process, the stored heat increasing with the absorbed solar radiation. The daily energy efficiency is around 47%.